COMMUNICATION COMPETENCIES AND PEDAGOGICAL APPROACHES INFLUENCING STUDENT HEALTH IN HIGHER EDUCATION INSTITUTIONS - Zafarbek Shavkatbekovich Khakikatbekov (International Scientific and Current Research Conferences, 2025)
In contemporary higher education settings, student health is not merely a function of biological or environmental factors but is profoundly influenced by the quality of interpersonal communication and pedagogical interactions. This article examines the intricate relationship between students’ communicative competencies and the implementation of pedagogical strategies that foster a supportive learning environment conducive to both mental and physical well-being. Drawing upon recent empirical studies, the paper highlights how the development of active listening, conflict resolution skills, and empathy, alongside the adoption of learner-centered pedagogical approaches, contributes to reduced stress, enhanced motivation, and overall holistic health. By integrating theoretical frameworks from educational psychology and health promotion, the study elucidates mechanisms through which communication and pedagogy intersect to shape students’ psychosocial resilience. The findings underscore the necessity for higher education institutions to prioritize communication skills training and adaptive pedagogical practices as integral components of student health initiatives.